Formulasi Penambahan Kacang Hijau Pada Susu Nabati Biji Cempedak (Artocarpus integer) Instan - Tri Elia Marpaung; Tri Rahayuni (FoodTech: Jurnal Teknologi Pangan, 2023)
Vegetable milk is processed from grains such as soybeans and red beans, but lately, grains also come from fruit seeds, although they specifically differ in the content of the majority of nutrients. The jackfruit seed is one of the trees whose sources can be developed into vegetable milk. In West Kalimantan, cempedak fruit seeds cannot always be found because they are classified as seasonal fruits, so instant powdered milk is the right choice to maintain its shelf life, knowing that it can be consumed anywhere. Modern technology supports the creation of instant vegetable milk, making it easier to consume, pack, and carry anywhere. This study aims to obtain the formulation of adding mung bean as a protein source that produces the best physicochemical and sensory characteristics of instant cempedak seed vegetable milk. The method used in this study was a randomized block design (RBD) with one factor, namely the formulation between mung bean and jackfruit seed notation (a) which consisted of 6 treatment levels. The results of the study concluded that the formulations of cempedak seeds and aloe vera produced the best formulations, namely formulation a5 (36:30), with the best chemical and sensory characteristics creating a protein content of 25.68%; water content of 10.86%; total dissolved solids 4.00 oBrix; pH 4.73; taste 3.90 (like); color 3.93 (like); aroma 3.63 (somewhat like); and overall 3.93 (kind of like it)